2005
DOI: 10.1007/s11745-005-1440-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α‐linolenic acid increases brain but not heart and liver docosahexaenoic acid levels

Abstract: Fish oil-enriched diets increase n-3 FA in tissue phospholipids; however, a similar effect by plant-derived n-3 FA is poorly defined. To address this question, we determined mass changes in phospholipid FA, individual phospholipid classes, and cholesterol in the liver, heart, and brain of rats fed diets enriched in flax oil (rich in 18:3n-3), fish oil (rich in 22:6n-3 and 20:5n-3), or safflower oil (rich in 18:2n-6) for 8 wk. In the heart and liver phospholipids, 22:6n-3 levels increased only in the fish oil g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 75 publications
8
27
1
9
Order By: Relevance
“…EPA normally competes with ARA to be incorporated into membrane phospholipids (Sun et al, 2008), an effect that is notorious when higher amounts of ALA are provided, such as in the case of ChO. Less competence is observed for SO and SIO, but irrelevant for CO. DHA is almost exclusively accumulated in the brain, retina and gonads (Innis and Dyer, 2002;Barceló-Coblijn et al, 2005). The presence of this n-3 LCPUFA in the liver reflects the active conversion of ALA into DHA, and its presence in plasma shows its active transport to the target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…EPA normally competes with ARA to be incorporated into membrane phospholipids (Sun et al, 2008), an effect that is notorious when higher amounts of ALA are provided, such as in the case of ChO. Less competence is observed for SO and SIO, but irrelevant for CO. DHA is almost exclusively accumulated in the brain, retina and gonads (Innis and Dyer, 2002;Barceló-Coblijn et al, 2005). The presence of this n-3 LCPUFA in the liver reflects the active conversion of ALA into DHA, and its presence in plasma shows its active transport to the target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…When the diet contains DHA, ALA did not contribute appreciably to DHA within brain phospholipids of adult rats (Demar et al, 2005). However, some recent results have suggested that DHA could be synthesized directly in the brain from ALA (Barcelo-Coblijn et al, 2005). We cannot confirm these results, since we were not able to measure desaturase activities in the brain (data not shown).…”
Section: Discussionmentioning
confidence: 60%
“…In many countries, however, the intakes of both a-linolenic acid (ALA; C18:3 n-3) and DHA (Burdge and Calder, 2005;Denomme et al, 2005) are lower than the current dietary recommendations (Simopoulos et al, 1999). Various dietary strategies have been proposed to increase their cellular level: (i) consumption of oils rich in ALA (Harper et al, 2006), but the rate of in vivo conversion of ALA to highly unsaturated fatty acids (FA) is low (Burdge and Calder, 2005;Hussein et al, 2005), and its effective conversion to DHA in mammalian tissues, although recently quantified in the plasma of rats as 10-fold higher than brain consumption rates (Igarashi et al, 2007), is controversial (Barcelo-Coblijn et al, 2005;Lin and Salem, 2005), because of the competition of multiple substrates for D6-desaturase (D' Andrea et al, 2002); (ii) consumption -E-mail: Vincent.Rioux@agrocampus-rennes.fr of fish, fish oil or microalgae oil (Geppert et al, 2005) directly providing the long-chain (n-3) derivatives; and (iii) consumption of both ALA and long-chain (n-3) derivatives, by using, for example, products from breeding animals that have been fed with extruded linseeds (Weill et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…En el cerebro la conversión de ALA en DHA es particularmente importante, especialmente porque este es el tejido que contiene el mayor contenido de DHA en el organismo (7,8). Es así como al estudiar la biotransformación del ALA se observa un incremento significativo de la formación de DHA, situación que no se observa con sus intermediarios (EPA y DPA) (37).…”
Section: Metabolismo Del Ala Y Conversión Enunclassified
“…Estudios realizados en animales Se han realizado numerosos estudios sobre la conversión del ALA en diferentes modelos animales (ratas, hámster, conejos, cerdos, primates, entre otros) los que han permitido establecer varios aspectos, siendo los más importantes; (i) el ALA se convierte en sus derivados metabólicos en muy baja cantidad (6 al 0,05%) y (ii) el ALA cuando es metabolizado se transforma rápidamente en EPA, pero no de igual forma en DHA, indicando limitaciones importantes dentro de la propia vía metabólica de los AGPICL ω-3 (37,39).…”
Section: Metabolismo Del Ala Y Conversión Enunclassified